The Combination Human and Cow Feces Biofertilizer to Improve the Soil and Water Quality in Pond of Pangasianodon hypophthalmus - Christine Natalina; Syafriadiman syafiadiman; Saberina Hasibuan (Jurnal Perikanan dan Kelautan, 2022)
Research was conducted from November to December 2019 at the peatland of Kualu Nenas Village, Tambang District, Kampar District, Riau Province. The purpose of this research is to get a comparison of the concentrations human and cow biofertilizer for chemistry parameter of soil and water. The method used in this study was the experimental method of using the Complete Random Design (CRD) one factor with five treatments and three replication. The treatment used were P0 (Without biofertilizer), P1 (20% human feces biofertilizer + 80% cow feces biofertilizer), P2 (40% human feces biofertilizer + 60% cow feces biofertilizer) P3 (60% human feces biofertilizer + 40% cow feces biofertilizer), P4 (80% human feces biofertilizer + 20% cow feces biofertilizer). The study was using 1x1x1,4 m peat ponds which were filled with 50 fishes that were maintained for 28 days. The results of this study showed a mixture of 80% human feces biofertilizer + 20% cow feces biofertilizer provides the best solution for chemical parameters of soil and water that soil pH is 6,95, N-Total 0,3733%, P-Total 0,6073%, K-Total 0,5133%, KBOT 63,90%, and C/N 23,80 then water temperature were about 27-29 0C, water pH were about 6-7, DO were about 3,6-6,0 mg/L, CO2 were about 20,78-32,97 mg/L, water nitrate were about 0,5150-4,2134 mg/L and orthophosphate were about 1,3047-4,7463 mg/L. The growth of striped catfish that maintained are absolute weight is 17,33 gram, absolute length is 4,433 cm, and survival rate 86%.